(untitled) (College of Basic Education Research Journal, 2026)
This research aims to explore the role of artificial intelligence (AI) as an innovative cognitive approach in enriching Islamic thought and renewing its curricula, highlighting the potential and challenges associated with its use in the fields of Islamic law and education. The research adopted a descriptive and analytical approach, drawing on previous studies and scientific literature, to analyze the relationship between AI and Islamic thought from a cognitive perspective, focusing on how to employ modern technologies in a manner consistent with Islamic values and principles. The results of the study demonstrated that AI represents an advanced cognitive tool that researchers can rely on to analyze Islamic law and intellectual texts more accurately and effectively and extract intellectual patterns and general principles. This contributes to the development of educational and research curricula in line with the requirements of the digital age. The results also demonstrated that Islamic thought possesses methodological flexibility that enables it to absorb and employ modern technologies, while preserving the Islamic legal and objective constants that form the foundation of intellectual and religious guidance. The study also pointed to a number of challenges that may face the use of artificial intelligence in this field, most notably the loss of human reasoning, the difficulty of accurately understanding the legal context, the potential for bias in the data used, and ethical issues related to digital fatwas and protecting the privacy of individuals and society. The study concludes that artificial intelligence can become a powerful strategic tool for enhancing scientific research and Islamic thought, by enabling researchers to develop innovative and advanced educational and intellectual curricula that keep pace with modern digital developments and enable the full use of its potential without compromising legal constants or objectives. This opens new horizons for reshaping the research and educational process in Islamic thought to ensure a balance between modernity and religious authority